2008
DOI: 10.1002/masy.200850723
|View full text |Cite
|
Sign up to set email alerts
|

Polysilanes. A New Route Toward High Performance EL Devices

Abstract: The discovery of a remarkable class of plastics that can conduct electricity has opened a new era of plastics science and technology that has just been recognized by the award of the 2000 Nobel prize for chemistry. They can be used to make a wide range of electronic devices such as transistors, light‐emitting diodes, solar cells and even lasers, through much simpler manufacture than conventional inorganic materials, increasing flexibility, reducing cost, and opening up new markets. Polysilanes are subject of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The electronic properties of polysilanes depend on the conformation of the silicon backbone, which can be affected by the substituents and temperature. 88,89 Polysilanes have been prepared by several methods, but in ROP the resulting polymer microstructure depends on the configuration of the monomer used for polymerization and so also on the mechanism of the process, which in turn depends on the catalyst or initiator used and the polymerization conditions. The Si-Si bonds can be broken apart by a variety of nucleophiles.…”
Section: Rop Of Cyclo-silanesmentioning
confidence: 99%
“…The electronic properties of polysilanes depend on the conformation of the silicon backbone, which can be affected by the substituents and temperature. 88,89 Polysilanes have been prepared by several methods, but in ROP the resulting polymer microstructure depends on the configuration of the monomer used for polymerization and so also on the mechanism of the process, which in turn depends on the catalyst or initiator used and the polymerization conditions. The Si-Si bonds can be broken apart by a variety of nucleophiles.…”
Section: Rop Of Cyclo-silanesmentioning
confidence: 99%
“…emphasized by specific investigations; (d) silicone crosslinking systems and mechanisms (peroxide, hydrosilylation, condensation, thiol-ene addition) for obtaining rubbers and other materials with applications in medicine, dentistry, construction, optoelectronics, etc.) [ 28 , 29 , 30 ]; (e) advanced polycarbosilane and polysilane structures [ 31 , 32 ]; and (f) series of hybrid polymeric materials, such as crosslinked siloxane-urethane, siloxane-chitosan or cellulose-siloxane structures [ 24 , 33 , 34 , 35 , 36 , 37 ], composites (silicone/silica, silicone/silica/titania, silicone/silica/Fe 2 O 3 ) adapted-by varying molecular weight, component ratios or crosslinking procedures to meet the requirements for certain applications (dentistry, actuators, etc.) [ 28 , 29 ].…”
Section: Context and Early Romanian Achievements In The Field Of Siliconesmentioning
confidence: 99%
“…It has been reported that donor and acceptor moieties via the bridge of σ‐orbitals is very likely involved in mediating the CT in such D‐π‐A system . Recently, organosilicon complexes have attracted much attention and become an important target due to their potential applications, such as conductor and semiconductor, light emitting diodes, high‐density optical data storage materials, electro luminescence devices and NLO materials ,. Nishihara and co‐workers have reported the photophysical properties of disilane‐bridged donor‐acceptor‐donor complexes and acceptor‐donor‐acceptor complexes, and revealed that these complexes displayed broad UV/Vis absorption bands assigned to intramolecular CT or π‐π* transition and excitation …”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Recently, organosilicon complexes have attracted much attention and become an important target due to their potential applications, such as conductor and semiconductor, [20] light emitting diodes, [21] highdensity optical data storage materials, [22] electro luminescence devices [23] and NLO materials. [24,25] Nishihara and co-workers have reported the photophysical properties of disilane-bridged donor-acceptor-donor complexes and acceptor-donor-acceptor complexes, and revealed that these complexes displayed broad UV/Vis absorption bands assigned to intramolecular CT or π-π* transition and excitation. [26] The increasing interest in diphenyldisilane compounds for NLO leads to various kinds of materials related to the intramolecular CT in conjugated systems.…”
Section: Introductionmentioning
confidence: 99%